Employability Skills among MARA Skills Training Institute Students in Malaysia - Kazilan, Fitrisehara (2008)
The main purpose of this research is to investigate the level of employability skills among students of IKM. This is a survey research. There were about 436 final year students from 13 IKM were chosen as a sample of this research. The data was collected by questionnaires which were adapted from Secretary’s Commission on Achieving Necessary Skills (SCANS). Descriptive analyses and inferences such as ANOVA, chi-square test and t-test were used to answer the research questions. The overall findings indicated that the employability skills among IKM students were average (M=3.86, SP=0.36) with basic skills (M=3.84, SP=0.48), thinking skills (M=3.81, SP=0.47), source skills (M=3.79, SP=0.49, information skills (M=3.74, SP=0.58), interpersonal skills (M=3.95, SP=0.51), system and technology skills (M=3.78, SP=0.67) and personal quality (M=4.13, SP=0.53). The research findings showed that there were significant differences between employability skills and courses taken [F(4,431)=3.041, p<0.05] and no significant correlation between employability skills and plan after they have graduated [X(1)=0.214, p>0.05]. The findings also showed that there were significant differences between employability skills for basic skills [t(434)=-2.532, p<0.05] and information skills and gender [t(434)=-2.127, p<0.05]. The study suggests that Technical and Vocational Education Department should incorporate employability skills in the student’s vocational curriculum to meet employer and industry’s demand in order to create self awareness among students in various fields. These employability skills will make them more prepared to enter world of work. The institutions and industries should collaborate to ensure the male and female trainees in vocational fields will be more productive and of high quality workers.